Hybrid Travel Intermediation in Small Island Tourism: Value Co-Creation between OTAs and Travel Agencies in Bali-Nusra - I Wayan Adi putra Ariawan; Finia Ribeiro; Elizabeth Barreto Araujo; Helio Brites da Silva; Margaretta Evy M.D. da Silva; Ariance Ana Lasibey (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
The rapid digitalisation of the tourism industry has transformed traditional distribution systems, raising questions about the evolving role of intermediaries in contemporary travel ecosystems. This study investigates the emergence of hybrid travel intermediation in small island tourism, focusing on the integration of Online Travel Agents (OTAs) and traditional travel agencies in the BaliÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Å“Nusa Tenggara (BaliÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬Å“Nusra) region, Indonesia. Adopting a qualitative multiple case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving tourists, travel agents, and tourism stakeholders. The findings reveal that tourism intermediation has shifted from a dichotomous ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œOTA versus travel agentÃƒÂ¢Ã¢â€šÂ¬Ã‚Â paradigm to a complementary and interdependent system. OTAs primarily function as digital enablers, facilitating efficiency, accessibility, and information transparency, while traditional travel agents provide relational value through trust, personalisation, and local knowledge. The study further identifies key mechanisms of value co-creation, including information integration, experience customisation, and continuous interaction throughout the travel journey. Importantly, the characteristics of small island tourism such as limited infrastructure and reliance on local networks reinforce the continued relevance of human intermediaries. The emergence of ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œhybrid tourists,ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â who combine digital and offline channels, highlights a shift towards multi-channel consumption behaviour. This study contributes to the literature by proposing the concept of hybrid travel intermediation and extending Service-Dominant Logic within a multi-actor tourism ecosystem. The findings offer theoretical insights and practical implications for tourism stakeholders seeking to balance digital transformation with relational service value in peripheral destinations